Diseño, implementación y evaluación de prácticas pedagógicas en un programa de Licenciatura con énfasis en inglés - Méndez, Pilar Esther; Bonilla, Ximena (Colombian Applied Linguistics Journal, 2016)
This article identifies the challenges lived in an attempt to a disciplinary integration in the subjects dedicated to teaching practice of a Bachelor of Arts in Education. This B.A. program declares an interdisciplinary curriculum. Through a model of mixed action research, supported on the theory of curriculum evaluation (Palos, 2000; Posner, 2004; Martinello y Cook, 2000), the diagnosis reveals a lack of articulation between theory and practice; a break- up between what is declared in the official curriculum towards the interdisciplinary relationships between fields of training and what happens in practice. That is, a disconnection on the horizons of training in teaching practices and problems in its direction and guidance. The research process allows, on the one hand, assessing information about how teachers, students and administrative assume interdisciplinarity in the process of teacher education. On the other hand, the process permitted to provide some guidelines aimed at encouraging interdisciplinary relationships among fields of training as a result. Those guidelines attempt to give coherence and validity to the problematic nucleus. Findings suggest that curriculum interventions based on the implementation of those guidelines provide a framework for more active participation of teachers and students to self-assessment and solution of specific problems.